Therapeutic effect of aged garlic extract on gingivitis in dogs - Takahashi, Kaori; Nango, Hiroshi; Ushijima, Mitsuyasu; Takashima, Miyuki; Nakamoto, Masato; Matsutomo, Toshiaki; Jikihara, Hiroshi; Arakawa, Nanami; Maki, Shinichiro; Yabuki, Akira; Endo, Yasuyuki; Yamato, Osamu (Frontiers in Veterinary Science, 2023)
Periodontal disease is one of the most common dental health problems in dogs. Clinical studies in humans have shown that aged garlic extract (AGE), which contains stable and water-soluble sulfurcontaining bioactive compounds, improves the symptoms of periodontal diseases. Our previous study demonstrated that oral administration of AGE in healthy Beagle dogs at 90 mg/kg/day for 12 weeks had no adverse effects such as hemolytic anemia, which is well known to occur as a result of ingestion of Allium species, including onions and garlic, in dogs. However, the therapeutic potential of AGE in canine periodontal disease remains unclear. Accordingly, we investigated the therapeutic effects of AGE in Beagle dogs with mild gingivitis. Feeding 18 mg/kg/day of AGE for 8 weeks resulted in the improvement of gingival index score, level of volatile sulfur compounds in exhaled air, and enzyme activity of periodontal pathogens without any adverse effects on clinical signs and hematological and serum biochemical parameters. Moreover, AGE increased the concentration of salivary cathelicidin, an antimicrobial peptide that contributes to the oral innate immune response. These results suggest that AGE could be a potential therapeutic agent for canine gingivitis.periodontitis based on their different clinical observations (7).